CULTURAL ACCULTURATION IN THE INTERIOR OF CHENG HO PANDAAN MOSQUE IN EAST JAVA - Fitriana, Tiara Rijayanti; Isfiaty, Tiara (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
The culture of Islam spreaders can be acculturated with local culture and affect the visual of the mosque. The research object is Cheng Ho Pandaan Mosque in Pasuruan. The research was conducted using qualitative method through observation and literature study. The results show that there is cultural acculturation in Cheng Ho Pandaan Mosque, it can be seen through interior elements and the use of colors. Chinese architectural principles influence the visual appearance of the mosque. The purpose of the research is to find out the form of implementation of cultural acculturation in Cheng Ho Pandaan Mosque, understand how to maintain cultural and religious identity simultaneously in a mosque. The research is useful to know the description of the balance of cultural elements in the mosque and can be used as an additional reference for interior designers to combine many cultures in one building.